(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Injuries and diseases of the musculoskeletal system are the second leading cause of disability and the third leading cause of death. According to WHO forecasts, the number of patients with this pathology will increase, which is associated with an increase in the average life expectancy of the population. In modern traumatology and orthopedics, great importance is attached to the pathology of large joints, in particular, the hip joint. The problem of treating patients with diseases and injuries of the hip joint is not only medical, but also socio-economic in nature.